The high burden of cholera in children: comparison of incidence from endemic areas in Asia and Africa. - Jacqueline L Deen; Lorenz von Seidlein; Dipika Sur; Magdarina Agtini; Marcelino E S Lucas; Anna Lena Lopez; Deok Ryun Kim; Mohammad Ali; John D Clemens (Public Library of Science (PLoS), 2008)
BACKGROUND: Cholera remains an important public health problem. Yet there are few reliable population-based estimates of laboratory-confirmed cholera incidence in endemic areas around the world. METHODS: We established treatment facility-based cholera surveillance in three sites in Jakarta (Indonesia), Kolkata (India), and Beira (Mozambique). The annual incidence of cholera was estimated using the population census as the denominator and the age-specific number of cholera cases among the study cohort as the numerator. FINDINGS: The lowest overall rate was found in Jakarta, where the estimated incidence was 0.5/1000 population/year. The incidence was three times higher in Kolkata (1.6/1000/year) and eight times higher in Beira (4.0/1000/year). In all study sites, the greatest burden was in children under 5 years of age. CONCLUSION: There are considerable differences in cholera incidence across these endemic areas but in all sites, children are the most affected. The study site in Africa had the highest cholera incidence consistent with a growing impression of the large cholera burden in Africa. Burden estimates are useful when considering where and among whom interventions such as vaccination would be most needed.